SOSIALISASI DAN PELATIHAN PEMBUATAN PAVING BLOCK DARI LIMBAH SAMPAH PLASTIK DI DESA LABUHAN KABUPATEN SUMBAWA - Adiasa, Iksan; Aldrin; Julkarnain, M.; Mashabai, Ismi; Robban, Farisan; Esabella, Shinta (Universitas Mataram, 2024)
Sumbawa is an area that has minimal waste processing, especially plastic. Processing plastic waste needs to be done to prevent freezing, especially on beaches. This is because plastic waste is waste that is difficult to decompose. One of the areas that produces a lot of plastic waste in Sumbawa is Labuhan Village. Therefore, efforts need to be made to minimize the amount of waste in Labuhan Village by processing it into paving blocks. The aim of this service activity is to provide outreach and training on making paving blocks from plastic waste. This is done to improve the human resources of the Village Community in minimizing existing Plastic Waste. The method used is through socialization, delivery of material and direct question and answer discussions to the community and direct training related to making plastic paving blocks. Before carrying out the training, the community was given pretest questions and ended with post-test questions. The results obtained from this activity are an increase in the ability of village residents to process plastic waste into paving block products. This can be seen from the increase in public understanding by 68% as seen from the comparison of the pretest and post-test results. Apart from that, the community is also able to directly instill the process of making paving blocks from plastic waste, so that the community can utilize this understanding by making it independently and making it a side business in minimizing the accumulation of plastic waste. This community service activity is able to provide understanding and abilities to village residents in processing plastic waste into paving blocks.